Characteristics and quantitative models for hydrocarbon generation-retention-production of shale under ICP conditions: Example from the Chang 7 member in the Ordos Basin. (1st November 2020) - Hou, Lianhua; Ma, Weijiao; Luo, Xia; Liu, Jinzhong
Highlights: Pyrolysis experiments conducted on large-capacity, semi-open pyrolysis reactor. Generation-retention-production under ICP for shales with varied TOC characterized. Quantitative model for oil/gas generation-retention-production under ICP established. Abstract: Shales with varying TOC content (0.5–26%) from the seventh member of the Triassic Yanchang Formation (abbreviated as Chang 7 shale) were artificially matured via semi-open pyrolysis to systematically study the characteristics of hydrocarbon generation, retention, and production under in-situ conversion process (ICP) conditions. The results show that with increasing Ro, the quantities of both generated oil and gas present an S-shape increase trend, with their generation rates reaching the maximum at 0.9 %Ro and 1.1 %Ro, respectively. The retention quantity and capability of oil and gas of shales first increase and then decrease as a function of thermal severity. With increasing TOC, larger amounts of oil and gas are retained, but the retention capability of the shale decreases. The shale simultaneously retains the largest amount of oil during the maximum oil generation period. The quantities of produced oil and gas share the same variation trend with the that of generated oil and gas, and the maximum oil and gas production rates are consistent with maximum generation rates. The greater the TOC, the greater the shale production potential. With increasing thermal maturity, the oil production potential of shales decreases slowly and then becomes relatively steady, while the gas production potential first changes slightly and subsequently decline rapidly. Based on the oil and gas generation-retention-expulsion characteristics, quantitative prediction models as a function of TOC and Ro are established, which will contribute to future engineering of the ICP.